The Interactions among Gold, Oil, and Stock Market: Evidence from S&P500 - Gokmenoglu, Korhan K.; Fazlollahi, Negar (Elsevier Science Bv, 2015)
The inter-relationship between financial and commodity markets is one of the most challenging issues for investors. The volatility in one market might affect the price index of the other market. The aim of this paper is to test whether gold price, oil price, gold price volatility (GVZ) and oil price volatility (OVX) have significant effect on stock market price index (GSPC) or not. In order to carry out the task, due to the properties of the data, the ARDL co-integration approach has been used to check the long-run relationship among OVX and GVZ; as proxies of oil and gold market volatility indexes; and S&P500 market price index. Obtained results indicate the presence of long-run equilibrium among the variables under investigation and reveal that S&P500 stock market price index converges to its long-run equilibrium level by 1.2% speed of daily adjustment by contribution of oil and gold market prices and their volatilities. (C) 2015 The Authors. Published by Elsevier B.V.
16th Annual Conference on Finance and Accounting (ACFA) -- MAY 29, 2015 -- Prague, CZECH REPUBLIC
Keywords: Gold price; Oil price; Stock price; ARDL; Bounds test